Digital preservation for libraries, archives, and museums - Corrado, Edward M. 1971-; Moulaison Sandy, Heather (Rowman & Littlefield, 2017)
This new edition of Digital Preservation in Libraries, Archives, and Museums is the most current, complete guide to digital preservation available today. For administrators and practitioners alike, the information in this book is presented readably, focusing on management issues and best practices. Although this book addresses technology, it is not solely focused on technology. After all, technology changes and digital preservation is aimed for the long term. This is not a how-to book giving step-by-step processes for certain materials in a given kind of system. Instead, it addresses a broad group of resources that could be housed in any number of digital preservation systems. Finally, this book is about “things (not technology; not how-to; not theory) I wish I knew before I got started.” Digital preservation is concerned with the life cycle of the digital object in a robust and all-inclusive way. Many Europeans and some North Americans may refer to digital curation to mean the same thing, taking digital preservation to be the very limited steps and processes needed to insure access over the long term. The authors take digital preservation in the broadest sense of the term: looking at all aspects of curating and preserving digital content for long term access.